Systematization of Nursing Assistance: Reality or utopia from the perspective of academics "Magalhães Barata" Nursing School - Neiva José da Luz Dias Júnior Júnior; Lourdes Oliveira Gomes; Mary Elizabeth de Santana; Sandra Helena Isse Polaro (Universidad de Alicante, 2017)
This study focus on a descriptive work by a qualitative approach in order to analyze the perception of the academics in Magalhães Barata Nursing School (MBNS) over systematization of nursing assistance (SNA). This research took place at Magalhães Barata Nursing School of Pará State University. Twenty nursing graduates were subject of this research. Collection of data was made by an interview composed of five open questions. There are four categories which emerged through the process: Defining SNA; The SNA teaching in MBNS and its trainee area difficulties; The importance of SNA to professional development and SNA:Reality or utopia?. It becomes evident the need for association between the academy and the health service so that the difficulties will be overcome in both.